Development and Validation of the Student Well-Being Scale for Elementary School Using Rasch Model Analysis - Widodo, Wahyu; Degeng, I Nyoman Sudana; Pali, Marthen; Hitipeuw, Imanuel (Universitas Ahmad Dahlan, 2024)
Efforts to realize student well-being are of particular concern in Indonesia. Unfortunately, a scale measuring student well-being for elementary school students is still scarce. This study aimed to develop and validate a scale for the well-being of elementary school students in Indonesia. The scale was developed based on the Student Well-being Model and analyzed using the Rasch Model. This study involved 414 respondents who were Grade 5 or Grade 6 elementary school students in Malang city. Based on the analysis of the Rasch model, there are 19 items (out of 28 items) whose values meet the criteria for outfit MNSQ, outfit ZSTD, and point measure correlation. This scale has a dimensionality value of 42.9%, item separation of 6.93, and item reliability of 0.98, and the results of the DIF analysis showed no bias toward gender or class identity. Overall, it can be concluded that the Student Well-being in Elementary Schools scale has good psychometric properties, so it is suitable for measuring student well-being in Elementary Schools.